2016
DOI: 10.18632/oncotarget.12169
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-552 enhances metastatic capacity of colorectal cancer cells by targeting a disintegrin and metalloprotease 28

Abstract: Colorectal cancer (CRC) is one of the most common prevalent cancer types worldwide. MicroRNAs (miRNAs or miRs) have been demonstrated to play crucial roles in the development, metastasis and drug resistance of CRC. In the present study, a strikingly elevated expression of miR-552 was determined in CRC tumor tissues and cells by a miRNA profiling analysis. Importantly, the gene of A Disintegrin And Metalloprotease (ADAM) family member 28 (ADAM28) was identified as a target of miR-552, which was further validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 41 publications
3
36
0
1
Order By: Relevance
“…However, the role of ADAM28 in colorectal cancer remains controversial [20,22]. Here, we provide evidence to show in our current functional study that ADAM28 appears to also play a pathogenic role in the metabolic syndrome.…”
Section: Discussionsupporting
confidence: 68%
“…However, the role of ADAM28 in colorectal cancer remains controversial [20,22]. Here, we provide evidence to show in our current functional study that ADAM28 appears to also play a pathogenic role in the metabolic syndrome.…”
Section: Discussionsupporting
confidence: 68%
“…The promotive role of miR‐552 in CRC was confirmed recently by Wang et al. and Cao et al. This paper showed that an understanding of the expression and function of miR‐552 in HCC might help to understand the underlying molecular mechanisms.…”
Section: Discussionsupporting
confidence: 53%
“…1 MicroRNAs (miRNAs) are sequences of small noncoding RNAs of 18-22 nt in length. 6 They manipulate the expression levels of more than 60% of human genes at the posttranscriptional level by binding to the 3′ untranslated regions (3′UTR) of their target messenger RNAs (mRNAs). 7 This repression enables them to participate in cellular events, including proliferation, apoptosis and movement.…”
Section: Introductionmentioning
confidence: 99%
“…The relative ratio of the net intensity of each sample normalized by the β‐tubulin internal control was calculated as densitometric arbitrary units (A.U.) that served as an index of relative expression of a protein of interest …”
Section: Methodsmentioning
confidence: 99%